Answer:
See explanation
Explanation:
Jenny solves
and finds the solutions are
and
![x=1.](https://img.qammunity.org/2020/formulas/mathematics/middle-school/hu849wd0pcsjtm12uo329t202ezhad3ljm.png)
So, she can write this equation as
![(x-(-3))(x-1)=0\\ \\(x+3)(x-1)=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/hxpii8g0n1dmjunfqawddbi0lgem2vlfsy.png)
The y-intercept is at
Substitute it into the previous equation:
![(0+3)(0-1)=3\cdot (-1)=-3](https://img.qammunity.org/2020/formulas/mathematics/middle-school/uu27kk0q44onrz7qk5lsfzv0s7u5rgqdla.png)
From the graph, she can see that y-intercept is at point (0,-3), so y-intercept -3 is the product of solutions to the quadratic equation.